HYDROTECHNICAL TUNNELS AT DAMS - Zafirovski Zlatko; Petkovska Marija (FACULTY OF CIVIL ENGINEERING AND ARCHITECTURE, UNIVERSITY OF NIŠ, 2023)
Performance of the construction work for each structure needs to be in accordance with a project documentation, for which a construction permit has been granted. Sometimes there’s a need for a change of basic design, not only for rough construction work, but for all construction works. In this paper hydrotechnical tunnels are mainly covered. First, there is a description of construction of one diversion tunnel, then the explanation of construction of two hydrotechnical tunnels from dams with accumulation, these dams are still being built in North Macedonia. The main part of this paper thesis is comparison between the changes in the construction work and the design of the tunnels.
Keywords: Structures, Diversion tunnel, Project documentation, Performance, Comparative analyses